Impact of treatment delay on mortality in ST-segment elevation myocardial infarction (STEMI) patients presenting with and without haemodynamic instability: results from the German prospective, multicentre FITT-STEMI trial - Scholz, Karl Heinrich (Eur Heart J, 2018)
AIMS: The aim of this study was to investigate the effect of contact-to-balloon time on mortality in ST-segment elevation myocardial infarction (STEMI) patients with and without haemodynamic instability. METHODS AND RESULTS: Using data from the prospective, multicentre Feedback Intervention and Treatment Times in ST-Elevation Myocardial Infarction (FITT-STEMI) trial, we assessed the prognostic relevance of first medical contact-to-balloon time in n = 12 675 STEMI patients who used emergency medical service transportation and were treated with primary percutaneous coronary intervention (PCI). Patients were stratified by cardiogenic shock (CS) and out-of-hospital cardiac arrest (OHCA). For patients treated within 60 to 180 min from the first medical contact, we found a nearly linear relationship between contact-to-balloon times and mortality in all four STEMI groups. In CS patients with no OHCA, every 10-min treatment delay resulted in 3.31 additional deaths in 100 PCI-treated patients. This treatment delay-related increase in mortality was significantly higher as compared to the two groups of OHCA patients with shock (2.09) and without shock (1.34), as well as to haemodynamically stable patients (0.34, P < 0.0001). CONCLUSIONS: In patients with CS, the time elapsing from the first medical contact to primary PCI is a strong predictor of an adverse outcome. This patient group benefitted most from immediate PCI treatment, hence special efforts to shorten contact-to-balloon time should be applied in particular to these high-risk STEMI patients. CLINICAL TRIAL REGISTRATION: NCT00794001.